Developing Partnership with Sports: How Do We Go About It - Lead or Response - Leung, C. (3rd International Forum on Elite Sport. Burleigh Court, Loughborough University, 9-11 September 2003, 2003)
Powerpoint-Präsentation zur Zusammenarbeit des Hongkong Sports Institute mit nationalen Sportverbänden.